PENENTUAN HARI BAIK PERNIKAHAN DENGAN MENGGUNAKAN TATAL DALAM PERSPEKTIF SOSIOLOGI - Zulfa Miftahu Rohmah; Ahmad Nurcholis (al-Afkar, Journal For Islamic Studies, 2022)
Marriage is a sacred bond between a man and a woman, when it is said Ijab Qabul means the marriage is valid and ready to enter a new level of life (household). One of the Javanese customs that is carried out before the wedding is to determine or look for the lucky day of Weton or Neptu for the bride and groom based on Javanese Primbon. The determination of the wedding day is based on the traditions found in the Nglebeng Village community. In this study, we will discuss how the process of determining the wedding day is carried out in Nglebeng Village using Weton calculations and using Javanese Sholichin tatal. Javanese Tatal is a formula to find out what day, wuku and month it is permissible and appropriate to carry out a wedding celebration. Researchers used qualitative research methods and case study approaches. This study uses Max Weber's theory, namely rational action which is included in the type of traditional action. The results of this study are that the tradition of determining the lucky day in marriage carried out by Nglebeng Village residents is a habit carried out by the local community before the marriage contract.